Toddler behavior, the home environment, and flame retardant exposure. (August 2020) - Sugeng, Eva J.; de Cock, Marijke; Leonards, Pim E.G.; van de Bor, Margot
Abstract: Toddlers are at increased risk of dust ingestion and subsequently flame retardant (FR) exposure because they often play close to the floor and mouth hands and objects. Exposure to some FRs have been associated to endocrine disruption and neurodevelopmental disorders. Previous research has shown higher FR concentrations in toddlers' serum and urine, but which toddler-behaviors influence exposure levels remains to be determined. We investigated how toddler-behaviors are associated to FRs in hand wipes (HWs) and saliva. Fifty 8-18 month-old children from the Linking EDCs in maternal Nutrition to Child health study, were visited at home. The child's behavior was observed and assessed using a questionnaire. Hand-to-object behavior frequency was associated with HW tris(chloroethyl) phosphate (TCEP), tris(1, 3-dichloroisopropyl) phosphate (TDCIPP), tris(phenyl) phosphate, tris(methylphenyl) phosphate, and resorcinol bis(diphenyl phosphate) levels above the detection limit. Children playing with electronics multiple times per week had higher TDCIPP HW levels compared to children playing with electronics once per month or never (p = 0.032 and p = 0.046). Frequent mouth-to-object and frequent mouthing a pacifier were associated with lower TDCIPP (p = 0.019) and tris(2-chloroisopropyl) phosphate (TCIPP) HW levels, respectively (p = 0.002–0.019). Exposure estimates based on hand-to-mouth behavior did not exceed the available reference doses. This is the first study investigating toddler-behavior in relation to FR hand loadings. Although a range of behaviors was investigated, only a few showed a relation with FR HW levels, suggesting that toddler-behavior might not alone be responsible for the elevated FR levels in children. It is therefore important to explore other pathways including dermal absorption and inhalation. Graphical abstract: Image 1 Highlights: First study on toddler-behavior in relation to OPFR and BDE209 hand loadings. Frequent hand-to-object behavior was associated with higher FR hand wipe levels. Frequent playing with electronics was associated with higher TDCIPP hand wipe levels. Cleaning frequency was not associated with hand wipe FR levels. Usage of some electronics devices had influence on hand wipe FR levels.